2005
DOI: 10.1007/s10681-005-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of European spelt wheat (Triticum aestivum ssp. spelta L. em. Thell.) revealed by glutenin subunit variations at the Glu-1 and Glu-3 loci

Abstract: High and low molecular weight glutenin subunit (HMW-GS and LMW-GS) compositions of 270 European spelts, 15 Iranian spelts and 25 bread wheat cultivars were analyzed by one-and two-dimensional gel electrophoresis. The results revealed a total of 22 HMW-GS alleles (4 at Glu-A1, 11 at Glu-B1 and 7 at Glu-D1) and 32 allele combinations among the three Glu-1 loci. Two major genotypes of HMW-GS: 1, 13+16, 2+12 and 1, 6.1+22.1, 2+12 were found to occur in Central European spelt wheat cultivars and landraces at higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 22 publications
1
28
1
3
Order By: Relevance
“…Genetic analysis showed that LMW-GSs were encoded by the complex Glu-3 loci on the short arms of homeologous group 1 chromosomes in hexaploid wheat (Singh and Shepherd 1988;Gupta and Shepherd 1990;Yan et al 1999). In the past, an increasing number of LMW-GS genes have been isolated and characterized from common wheat (D'Ovidio and Masci 2004) and high allelic variations have been identified at the Glu-3 locus (Gianibelli et al 2002;Yanet al 2003a,b,c;An et al 2005;Li et al 2006). A recent focus has been to isolate new LMW-GS genes from wheat related species, e.g., Triticum boeoticum (Lee et al 1999), T. monoccocum , Aegilops tauschii ( Johal et al 2004;Pei et al 2007), and T. dicoccoides (Q.…”
mentioning
confidence: 99%
“…Genetic analysis showed that LMW-GSs were encoded by the complex Glu-3 loci on the short arms of homeologous group 1 chromosomes in hexaploid wheat (Singh and Shepherd 1988;Gupta and Shepherd 1990;Yan et al 1999). In the past, an increasing number of LMW-GS genes have been isolated and characterized from common wheat (D'Ovidio and Masci 2004) and high allelic variations have been identified at the Glu-3 locus (Gianibelli et al 2002;Yanet al 2003a,b,c;An et al 2005;Li et al 2006). A recent focus has been to isolate new LMW-GS genes from wheat related species, e.g., Triticum boeoticum (Lee et al 1999), T. monoccocum , Aegilops tauschii ( Johal et al 2004;Pei et al 2007), and T. dicoccoides (Q.…”
mentioning
confidence: 99%
“…The gene copy numbers of LMW-GS have been estimated to vary from 10-15 to 35-40 in hexaploid wheat (Zhu and Khan 1999;Shewry et al 2003). The allelic variations of LMW-GS are also closely related to different dough properties in wheat cultivars (Payne and Lawrence 1983;An et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Este par de subunidades no se ha descrito entre espeltas españoles (Rodríguez-Quijano et al, 1990;Caballero et al, 2001) y tampoco entre espeltas de Europa Central (Yan et al, 2003;An et al, 2005). No obstante, la Dra.…”
Section: Discusión 113unclassified
“…Y en el estudio de Morgunov et al (1993) donde se analizan 1.380 cultivares de trigo panadero de todo el mundo, se encontraron frecuencias cercanas al 31 % para las tres HMW-GS 1, 2* y nula. En cambio, analizando colecciones de trigo espelta españolas (Rodríguez-Quijano et al, 1990;Caballero et al, 2001) y colecciones de espeltas europeos (Yan et al, 2003;An et al, 2005) se encontraron altas frecuencias de esta subunidad (en torno al 85 %).…”
Section: Calidad Del Granounclassified
See 1 more Smart Citation